Attitudes Toward Striving for Quality and Length of Life Among Patients With Advanced Cancer and a Poor Prognosis. Issue 11 (6th November 2022) - van der Velden, Naomi C.A.; van Laarhoven, Hanneke W.M.; Nieuwkerk, Pythia T.; Kuijper, Steven C.; Sommeijer, Dirkje W.; Ottevanger, Petronella B.; Fiebrich, Helle-Brit; Dohmen, Serge E.; Creemers, Geert-Jan; de Vos, Filip Y.F.L.; Smets, Ellen M.A.; Henselmans, Inge
Abstract : PURPOSE: When deliberating palliative cancer treatment, insight into patients' attitudes toward striving for quality of life (QL) and length of life (LL) may facilitate goal-concordant care. We investigated the (1) attitudes of patients with advanced cancer toward striving for QL and/or LL and whether these change over time, and (2) characteristics associated with these attitudes (over time). METHODS: We performed a secondary analysis of a randomized controlled trial on improving shared decision making (SDM), without differentiation between intervention arms. Patients (n = 173) with advanced cancer, a median life expectancy of < 12 months without anticancer treatment, and a median survival benefit of < 6 months from systemic therapy were included in seven Dutch hospitals. We used audio-recorded consultations and surveys at baseline (T0), shortly after the consultation (T2), at 3 and 6 months (T3 and T4). Primary outcomes were patients' attitudes toward striving for QL and LL (Quality Quantity Questionnaire; T2, T3, and T4). RESULTS: Overall, patients' attitudes toward striving for QL became less positive over 6 months ( P < .01); attitudes toward striving for LL did not change on group level. Studying individual patients, 76% showed changes in their attitudes toward striving for QL and/or LL at some point during the study, which occurred in various directions. More helplessness/hopelessness ( P < .001), less fighting spirit ( P < .05), less state anxiety ( P < .001), and more observed SDM ( P < .05) related to more positive attitudes toward striving for QL. Lower education, less helplessness/hopelessness, more fighting spirit, and more state anxiety ( P < .001) related to more positive attitudes toward striving for LL. CONCLUSION: Oncologists may explore patients' attitudes toward striving for QL and LL repeatedly and address patients' coping style and emotions during SDM to facilitate goal-concordant care throughout the last phase of life.